Facial clefts in the west of Scotland in the period 1980-1984: epidemiology and genetic diagnoses. Issue 2 (February 1994) - FitzPatrick, D R; Raine, P A; Boorman, J G
Abstract : Two hundred and eighty six cases of cleft lip, cleft palate, or both were identified in a study attempting complete ascertainment of babies with facial clefts born to women resident in the west of Scotland in a five year period beginning 1 January 1980. The total birth prevalence (TBP) of these defects over this period was 1.53 per 1000. The TBP for cleft lip with or without cleft palate (CL[P] was 0.74 per 1000 and for cleft palate (CP) was 0.79 per 1000; 26% of CL[P] and 39.5% of CP cases had one or more major congenital anomaly associated with their facial cleft and in over half of these cases a specific genetic or syndrome diagnosis could be made. In comparison to previous European reports this study shows a high incidence of associated abnormalities and a remarkably low ratio of CL[P]:CP cases.